Teachers’ Strategies for Shaping Islamic Character in Elementary School Students with Special Needs - Tania Umairah (Indonesian Journal of Character Education Studies, 2025)
Background: The formation of Islamic character among elementary students with special needs requires contextual, structured, and consistent strategies across school and family settings. Objective: To analyze teachers’ strategies for shaping the Islamic character of ABK at Fatma Kenanga Elementary School, Bengkulu City, and to map enabling and hindering factors. Method: Qualitative case study; purposive sampling of teachers and the principal. Data were collected through semi-structured interviews, focused observations, and document analysis, and analyzed using Miles and Huberman’s framework. Results: Character building employed four approaches: (1) exemplary conduct embedded in lesson plans and daily routines; (2) reinforcement of habitual practices; (3) social modeling; and (4) educative disciplinary measures. Implementation occurred daily with monthly character targets. Observable outcomes included worship practices, environmental stewardship, honesty (with variability), and discipline (persistent challenges with neatness after breaks). Supporting factors included educator solidarity and the relative ease of habit formation; family and neighborhood influences were ambivalent. Conclusion: When applied consistently and aligned with parental support, the combined strategies effectively strengthen the Islamic character of students with special needs. Contribution: This study proposes an integrative, operational framework that merges modeling, behaviorist reinforcement, and social learning for inclusive Islamic character education in elementary schools, together with practical guidance (daily routines, monthly targets, reinforcement, and educative sanctions) and an empirical basis for evaluating and developing ABK-friendly school policies.